2020
DOI: 10.2147/idr.s259914
|View full text |Cite
|
Sign up to set email alerts
|

<p>Detection and Control of Biofilm Formation by <em>Staphylococcus aureus</em> from Febrile Neutropenic Patient</p>

Abstract: Introduction Febrile neutropenia (FN) is the evolution of fever in a patient with neutropenia over 38.0°C. Neutropenia is diagnosed when absolute neutrophil count (ANC) <1500 cells/µL. FN represents a common complication of cancer treatment. Hence, it is featured to be a major cause of morbidity and mortality in cancer patients. Staphylococcus aureus is one of the most important microorganisms isolated from the blood of febrile neutropenic patients. Infections caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The present study revealed that the occurrence rates of biofilm-producing genes are much lower than the results observed in the CRA and CVMP tests. Similar findings were reported by previous studies [ 44 , 45 ], however, the high and similar prevalence rates of biofilm-producing S. aureus observed in the qualitative, quantitative, and molecular assays were recorded in previous studies [ 10 , 46 , 47 ]. This discrepancy could be explained by the different factors that are associated with biofilm formation in the S. aureus isolates.…”
Section: Discussionsupporting
confidence: 91%
“…The present study revealed that the occurrence rates of biofilm-producing genes are much lower than the results observed in the CRA and CVMP tests. Similar findings were reported by previous studies [ 44 , 45 ], however, the high and similar prevalence rates of biofilm-producing S. aureus observed in the qualitative, quantitative, and molecular assays were recorded in previous studies [ 10 , 46 , 47 ]. This discrepancy could be explained by the different factors that are associated with biofilm formation in the S. aureus isolates.…”
Section: Discussionsupporting
confidence: 91%
“…Among the tested strains, 37.5% were positive for icaA, and 22.9% were positive for icaD; however, only 50% of biofilm-producers carried either the icaA or icaD genes. 64 Similarly, no correlation among methicillin-resistance and biofilm-production was seen in the reports of Knobloch et al (including n=128 icapositive isolates, with utilizing CRA plates and the microtiter plate method) 65 and Mathur et al (where n=152 Staphylococcus spp. were tested using the microtiter plate method).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 95%
“…12 As biofilm is one of the major causes of amplifying antibiotic resistance, hence biofilm detection helps in investigating the severity of infection by S. aureus. 13 This study focused on general relationship between biofilm production and multidrug resistance in S. aureus isolates, and its effect on recommended antimicrobials. Penicillin, in general, was ineffective against all isolates.…”
Section: Discussionmentioning
confidence: 99%